Seasonality and geographical distribution of Kawasaki disease among Black children in the Southeast United States - Padilla, Luz A.; Idigo, Adeniyi J.; Maxwell, Kathryn; Lau, Yung; Wiener, Howard W.; Shrestha, Sadeep (Frontiers in Pediatrics, 2023)
Introduction: Kawasaki Disease (KD) is a leading cause of pediatric acquired heart disease in the United States, affecting up to 7,000 children annually. Seasonal variation, an epidemiological characteristic of KD, has previously been reported predominantly among Asian children; however, little is known about the epidemiology and seasonality of KD of Black children within the US. Methods: Electronic medical records were abstracted from 529 hospitalized KD patients admitted to a single tertiary center in Alabama between 2005-2019. Medical charts were reviewed to confirm KD diagnosis following American Heart Association criteria. Cases were stratified by the month of diagnosis date to assess seasonality, and statewide distribution of incidence is reported at county level using geographical spatial analysis. Comparisons were performed between Black and White KD patients. Results: The average number of KD cases per year was 35. Approximately, 60% were males and 44% were White (N=234), 45% were Black (N=240) and 11% were other races (N=55). Blacks were younger than Whites at KD admission (median age 32 vs 41 months respectively, p 0.02). Overall, the highest rates of cases occurred between January and April. When stratifying by race, cases started to rise in December among White children with the highest rates between February and April with a peak in March. Among Black children cases were high during the winter season (January-April) with a peak in April. Similarly high rates also occurred in June, July and November. There were no differences in geographical distribution of cases by race. Conclusion: KD incidence among Whites in Alabama follows a seasonal cycle similar to other regions in the US. However, sustained incidence and additional peaks outside of the usual KD seasonality were seen among Black children with KD. Further studies are needed to investigate differential triggers between races.